Glutamate Cotransmission in Cholinergic, GABAergic and Monoamine Systems: Contrasts and Commonalities - Trudeau, Louis-Eric; El Mestikawy, Salah (Frontiers in Neural Circuits, 2018)
Multiple discoveries made since the identification of vesicular glutamate transporters (VGLUTs) two decades ago revealed that many neuronal populations in the brain use glutamate in addition to their “primary” neurotransmitter. Such a mode of cotransmission has been detected in dopamine, acetylcholine, serotonin, norepinephrine and surprisingly even in GABA neurons. Interestingly, work performed by multiple groups during the past decade suggests that the use of glutamate as a cotransmitter takes different forms in these different populations of neurons. In the present review, we will provide an overview of glutamate cotransmission in these different classes of neurons, highlighting puzzling differences in (1) the proportion of such neurons expressing a VGLUT in different brain regions and at different stages of development, (2) the sub-cellular localization of the VGLUT, (3) the localization of the VGLUT in relation to the neurons' other vesicular transporter, and (4) the functional role of glutamate cotransmission.